2019
DOI: 10.23923/rpye2019.01.169
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators in Higher Education: analysis of psychosocial factors of students

Abstract: The objective is to determine the influence of substance consumption, emotional intelligence, and academic context on the two main indicators of the quality of university education: academic achievement and degree of satisfaction. Participants in the study were 202 students (82.2% female; mean age 21.83 years). Data were collected with a questionnaire including six parts: sociodemographic data, substance consumption, levels of satisfaction, academic context, academic performance (calculated by averaging the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The findings in this study entail some educational and health implications of scope. Students in the university stage are especially vulnerable to the adoption of self-handicapping and defensive pessimism strategies [36] because of the many academic, social, emotional, and economic challenges they must manage during this period, which may damage their psychological well-being [87,88] in case of failure. In effect, the recurrent use of self-handicapping is associated with important damages, not only for academic performance [7], but also for the student’s psychological health (e.g., decreased self-esteem, social rejection, increased depressive symptoms, reduced satisfaction with life) [5,89,90].…”
Section: Discussionmentioning
confidence: 99%
“…The findings in this study entail some educational and health implications of scope. Students in the university stage are especially vulnerable to the adoption of self-handicapping and defensive pessimism strategies [36] because of the many academic, social, emotional, and economic challenges they must manage during this period, which may damage their psychological well-being [87,88] in case of failure. In effect, the recurrent use of self-handicapping is associated with important damages, not only for academic performance [7], but also for the student’s psychological health (e.g., decreased self-esteem, social rejection, increased depressive symptoms, reduced satisfaction with life) [5,89,90].…”
Section: Discussionmentioning
confidence: 99%
“…Prior academic achievement was based on students' high school GPA, entrance exam, university credits and prior performance at university. Prior academic achievement was positively correlated with academic performance within 10 studies and showed typical to strong effects (Merchán Clavellino et al, 2019; Nelson, 2016; Ribeiro et al, 2019; Rodríguez et al, 2017; van Rooij et al, 2018; Wright et al, 2013; Zhou et al, 2015). Only one study showed a weak relationship between prior academic achievement and academic performance (Bailey & Phillips, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In total, seven studies investigated the relationship between negative emotions, positive emotions or emotional intelligence with academic performance. Positive affect, positive emotional functioning, and emotional intelligence showed weak to strong positive correlations with academic performance (Sadeghi Bahmani et al, 2018; Krumrei‐Mancuso et al, 2013; Lee et al, 2010; Merchán Clavellino et al, 2019; Song et al, 2010). In contrast, negative emotional functioning showed strong negative relationships with academic performance and negative affect showed weak correlations with academic performance (Sadeghi Bahmani et al, 2018; Bailey & Phillips, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…According to James et al (2010), some subgroups of students should be monitored closely, as the literature shows that the experience students have in their first year varies significantly depending on students' backgrounds. Thus, universities should consider improving their mechanisms of collecting information to allow for early identification, support, and monitoring of students at risk of dropping out (Merchán et al, 2019), showing high level of disengagement and low academic achievement.…”
Section: Practical Implicationsmentioning
confidence: 99%